A nova agenda da grande indústria: uma análise da indústria 4.0 com base em documentos e materiais de divulgação do projeto alemão Plattform Industrie 4.0 - Arias, Alexandre Peres (2020)
This dissertation analyses the Industry 4.0 project through reports, documents and advertising material from the German program Plattform Industrie 4.0. The objective is to understand how the ideas around Industry 4.0 are built, molded and projected towards a redemptive future and determined by technological advances in production. To this end, reports and documents from the Industry 4.0 platform in Germany, Plattform Industrie 4.0, were consulted, seeking to understand: the historical and economic background of Industry 4.0, the main actors involved, the dynamics of the relationship between government and companies and some of the commercial strategies to expand the market to Industry 4.0 products. In order to analyze such aspects of Industry 4.0, a parallel is drawn with the development of the field of Artificial Intelligence and seeks to show similarities between both, especially in the association that such discourses make between technological progress and human progress. In addition, it is observed that there are deterrence strategies that project distant futures and conditioned by technology in order to mobilize resources and support for their projects. Such strategies are identified in the formation of Artificial Intelligence and elements of Industry 4.0. In this sense, it uses the literature in the field of Science, Technology and Society to investigate how technological determinism manifests itself and, moreover, how it conceals aspects of the social relations of production in technological artifacts. It also addresses how the term Industry 4.0 is associated with the proposal for a Fourth Industrial Revolution that proposes to be universal, automated and disruptive and seeks to identify some of its ielements associated with the construction of a neoliberal agenda. Finally, reflections on the prospects for work are given given the projections and realities of Industry 4.0 such as the possibilities of job destruction through automation and the new configurations of digital work.